2003
DOI: 10.2165/00128071-200304120-00004
|View full text |Cite
|
Sign up to set email alerts
|

Racial (Ethnic) Differences in Skin Properties

Abstract: Racial (ethnic) differences in skin properties may explain racial disparities seen in dermatologic disorders and provide insight into appropriate differences in the management of these disorders. However, racial differences in skin have been minimally investigated by objective methods and the data are often contradictory. Objective methods studied include transepidermal water loss (TEWL), water content (WC), corneocyte variability, blood vessel reactivity, elastic recovery/extensibility, pH gradient, lipid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
138
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(147 citation statements)
references
References 35 publications
5
138
3
1
Order By: Relevance
“…It is well known that genetic background is the first determinant of skin characteristics [20], but recent studies showed that environmental factors (climate, food intake, life style, etc.) affect acquired skin features [21] [22] [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that genetic background is the first determinant of skin characteristics [20], but recent studies showed that environmental factors (climate, food intake, life style, etc.) affect acquired skin features [21] [22] [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although IVL is not actually invariant in Europe, F ST is still quite high among continents, and the locus possesses a unique haplotype structure with at least four SNPs in perfect linkage disequilibrium, leading to both high and low values of Tajima's D in different populations, based largely on the frequencies of these haplotypes. Given its role in the epidermis and its remarkable geographically structured polymorphism, we hypothesize that IVL alleles may contribute to the pronounced differences in hair or skin morphology observed among populations (Wesley and Maibach 2003;Loussouarn et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic skin types are known to differ in their morphological and physiological features [1]. The most obvious ethnic skin difference relates to skin color which is dominated by the presence of (different quantities and types of) melanin [2].…”
Section: Introductionmentioning
confidence: 99%